Assistance for Santri-Friendly Islamic Boarding School (Bullying and Sexual Violence Free) at Al-Amin Islamic Boarding School Mojokerto - Muhammad Farid Ilhamuddin; Ahmad Abdullah Zawawi; Lutfi Saksono; Ainur Rifqi (ABISATYA : Journal of Community Engagement, 2025)
The rise of bullying and violence in Islamic boarding schools, especially in the Mojokerto area, shows the need for more effective prevention efforts. Although some Islamic boarding schools have implemented character learning and internal policies, specific steps to protect students are still limited. This problem is the background for the emergence of a student-friendly Islamic boarding school mentoring program at the Al-Amin Islamic Boarding School in Mojokerto. The implementation of the service program at the Al-Amin Islamic Boarding School in Mojokerto is carried out through three stages, namely preparation, implementation, and evaluation. The data collection method was carried out by a mixed method which included participatory observation, structured interviews, documentation, and questionnaires, with the main focus on preventing bullying and sexual violence, establishing student-friendly Islamic boarding school and increasing the capacity of administrators, caregivers, and ustaz/ustazah. The "Student-Friendly Islamic Boarding School Assistance" activity has succeeded in building a socio-cultural model that focuses on creating a boarding school environment free of bullying and sexual violence through education, peer support, workshops, and the Islamic boarding school's internal system. The results of the evaluation showed an improvement in all aspects of knowledge, from the category of sufficient in the pre-test to very good in the post-test, with an average score of 4.4–4.5. This program is effective in increasing participants' understanding and awareness related to sexual violence, bullying, and the concept of student-friendly Islamic boarding school The implementation of the program faces several challenges. However, the enthusiastic response of participants and the support of caregivers opened up opportunities for program development, so that other Islamic boarding school could be replicated as needed.